Exploring the Implementation and Impact of Community Policing Strategies in Indonesia: A Case Study of Jakarta - Novianto, Ryno (Journal of Public Representative and Society Provision, 2023)
This paper critically discussed the practise and consequences of the community policing in Jakarta Indonesia, using case study method of research. Derived from the literature on social capital, bureaucratic policing, and participatory policing, the study focuses on the issues of trust and information exchange, lack of resources, police ranks and hierarchy, as well as people’s awareness. They highlight important shortcomings which have limited the success of community policing such as; inadequacy of resources and the challenges of a systemized policing structure. The research also reveals severe lack of public knowledge concerning community policing thereby hampering community involvement and participation. This is the sum up of the research that indicate that for community policing to embraced and work well, there need to be decentralisation, proper resource provision and more awareness creation. Consequently, they advance theoretical knowledge to the theory of community policing and provide recommendations concerning its application in heterogeneity socio political situation.